Physical characteristics of cashew apples from dwarf cashew (Anacardium occidentale L.) clones as a function of environmental and temporal variation (2018)
Cashew apple physical quality variables include different external characteristics, such as appearance, size, color, shape, and firmness, among others, which are very important in commercialization because they are the first characteristics perceived by consumers, who usually buy what attracts them most. The objective of this study was to evaluate the influence of the region, production year and genotype on the physical characteristics of dwarf cashew cashews (cashew apple + nut). The experiment design was completely randomized in a factorial scheme with repeated measurements over time, applying the confounding technique, with three clones (CCP 09, BRS 265 and PRO 555-1) in two different regions, sertão (Alto Santo-CE) and coast (Beberibe-CE), with four replications, collected in 2013 and 2014. In the laboratory, the cashews were evaluated for total mass (nut and cashew apple) (g), nut and cashew apple mass (g), length (mm), apical and basal diameters of the cashew apple (mm) and firmness of the cashew apple (N). It was observed that the region and the production year influenced the physical quality of the cashews. Among the clones that were studied, CCP 09 was the only one that presented a similar behavior in both regions, showing that it can obtain satisfactory quality in different environments. The other clones differed, presenting superior physical quality on the coast. In the sertão region, the best adapted clone was CCP 09 and, on the coast, it was the PRO 555-1 clone.